Late relapse of multiple myeloma presenting as a right atrial mass. (November 2014) - Behzadnia, Neda; Sheybani-Afshar, Faezeh; Hossein-Ahmadi, Zargam; Ansari-Asl, Zahra; Sharif-Kashani, Babak; Dorudinia, Atosa
Intracardiac involvement is a rare presentation of relapsed multiple myeloma. We present a case of lobulated mass in the wall of the right atrium, with extension to the inferior vena cava and obliteration and encasement of the interatrial septum in a 57-year-old man, a known case of multiple myeloma, with progressive exertional dyspnea and anasarca.